NEW ANTIVIRAL DRUG TRIAZID. RESULTS OF FIRST PHASE OF CLINICAL TRIAL - E. G. Deyeva; Yu. I. Shevchik; A. A. Shaldghan; K. A. Zagorodnikova; A. A. Tumashov; A. V. Baklykov; S. K. Kotovskaya; O. N. Chupahin; V. N. Charushin; V. L. Rusinov; D. S. Kopchuk (Разработка и регистрация лекарственных средств, 2019)
The paper contains а results of the study of the pharmacokinetics, tolerability and safety of a new influenza drug Triazide in several dose regimens conducted on healthy volunteers. The convenient method for the determining the Triazide in blood plasma and urine by the HPLC have been proposed for the using in this study. There was no reliable statistical relationship between drug intake, undesirable clinical events and changes in laboratory parameters. A study of the pharmacokinetics have been showed that Triazide in the blood plasma was found on average after 0.5 hours, the curve of decrease in concentrations was two-phase, the half-life in the first phase was 1.5-4.0 hours. The maximum concentrations with increasing dose increased in direct proportion. With an increase in the daily dose, the maximum concentration was reached earlier. At the same time, no significant cumulation was observed with prolonged use. In the study, Triazide was well tolerated by all participants in all studied dose regimens. Preferred regimens that provide maintenance of effective and safe concentrations, appearances were 300 mg two and three times a day.